The geographic accessibility of child care subsidies and evidence on the impact of subsidy receipt on childhood obesity - Chris M. Herbst; Erdal Tekin (Institute for the Study of Labor (IZA), 2011)
This paper examines the impact of the spatial accessibility of public human services agencies on the likelihood of receiving a child care subsidy among disadvantaged mothers with young children. In particular, we collect data on the location of virtually every human services agency in the U.S. and use this information to calculate the approximate distance that families must travel from home in order to reach the nearest office that administers the subsidy application process. Using data from the Kindergarten cohort of the Early Childhood Longitudinal Study (ECLS-K), our results indicate that an increase in the distance to a public human services agency reduces the likelihood that a family receives a child care subsidy. Specifically, we estimate an elasticity of subsidy receipt with respect to distance of -0.13. The final section of the paper provides an empirical application in which we use variation in families' travel distance to identify the causal effect of child care subsidies on children's weight outcomes. Our instrumental variables estimates suggest that subsidized child care leads to sizeable increases in the prevalence of overweight and obesity among low-income children.
urn:nbn:de:101:1-201110263684
Keywords: I12; I18; J13; R53; 330; child care; subsidy; obesity; Kinder; Sozialpolitik; Sozialer Dienst; Kinderbetreuung; Entfernung; Körpergewicht; USA